PERKEMBANGAN TENGKULUK DI KOTA JAMBI TAHUN 1946 - 2017 - Yaziva, Ikrima; Karmela, Siti Heidi (Universitas Batanghari Jambi, 2022)
The purpose of this study was to determine the development of Tengkuluk in Jambi City in 1946 – 2017. The research method used is the historical method because it collects historical sources effectively, evaluates them critically and presents a written synthesis of the results achieved. Based on the results of the study, the tengkuluk became a separate identity for women in Jambi. According to history, the tengkuluk cloth has existed since the 7th century, which at that time was used by Malay women to attend a traditional event or during farming activities such as in the fields and fields. Not just as a head covering, in fact the tengkuluk cloth has a deeper meaning. Jambi is rich in culture which is not widely known by the public. The city of Jambi, which is located on the east coast in the central part of Sumatra Island, has a Malay culture since ancient times. One proof of the Malay cultural customs in Jambi is the legacy of the traditional head covering called tengkuluk for women. Tengkuluk is the identity of Malay women. The tradition of covering the head or tengkuluk existed before the Jambi community knew Islam. At that time, the tengkuluk was only used as an accessory or a headdress as a beauty for Jambi Malay women, which was used as a head covering at parties, or on big days. The Tengkuluk is also used as a head restraint from the burdens of typing to put luggage on the head or as a head protector from the scorching heat of the sun when Malay women go to farming or berumo at that time. As a form of culture, the Tengkuluk has undergone various changes to date such as the development of public perception. about the neck. For women who wear the hijab, using the nape of the neck is to first use the hijab to cover the hair, ears and neck. Then just put the neck on the top of the head. Changes also occur in terms of the materials used in the elements found in the tengkuluk.